QUALIDADE DO MEL DE ABELHA PRODUZIDOS PELOS INCUBADOS DA IAGRAM E COMERCIALIZADO NO MUNICIPIO DE MOSSORÓ/RN - Edna Maria Mendes Aroucha; Alan Jhon Fonseca de Oliveira; Glauber Henrique Sousa Nunes; Patrício Borges Maracajá; Maria Célia Aroucha Santos (Revista Caatinga, 2008)
This experiment had for objective to evaluate some parameters of quality of the bee honey (Apis mellífera L.) produced by IAGRAM and commercialized in the city of Mossoró-RN. For this, 19 honey samples had been collected in the local market, these were analyzed, in the Chemistry Laboratory of the Universidade Federal Rural do Semi-Árido (UFERSA), how much to the color, humidity, total acidity, reducing sugars, apparent sucrose and diastase activity. It was utilized districted statistics for analysis of date, with shunting line standard, reliable interval and distribution of frequency. The honeys sample presented the colors clearly extra amber (5,2%), amber (5,2%) and dark amber (89,4%). The honey samples presented normal standard established for the Brazilian Legislation as humidity percentage (14,3 18.6%) and reducing sugars (66,9 75.0%). About 5,2% and 42% of the analyzed honey samples, not presented, respectively, apparent sucrose content and total acidity, as the standard established for commercialization as floral honey. The diastase activity was remained inside of the quality standard.